(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2019)
In the work research published in USA in the 1970s, the universities were regarded as organisations qualified as “organised anarchies” or “loosely coupled systems” which were considered host to “unclear technologies”. This paper confronts these concepts with the recent evolution of the piloting way of European higher education. The empirical material for this paper comes from the analysis of texts and reforms initiated in universities in Belgium, in UK and in France. The paper will show the effects of standardization instruments (learning outcomes approach and introduction of the ICT in the management of the academic work) on academic profession and how these instruments generate a deep interdependence between all the segment of the university. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.